2016
DOI: 10.1155/2016/2579345
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Two Purification Methods on the Immunogenicity of Recombinant Outer Membrane Protein H ofPasteurella multocidaSerovar A:1

Abstract: Recombinant outer membrane protein H (rOmpH) of Pasteurella multocida strain X-73 can be purified using affinity chromatography but this adversely affects its immunogenicity. The current study presents the results from an intervention study comparing the immunogenicity of rOmpH purified using electroelution with rOmpH purified using affinity chromatography and native OmpH purified using electroelution and a nonimmunized control group. Chickens immunized with rOmpH purified using electroelution produced the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Furthermore, rCP-SCMV in highly purified, specific, and high concentration form was obtained with the use of a purification technique based on eletroelution followed by concentrated protein. Comparing our results with those of other similar studies (Abdel-Salam et al 2014;Thanasarasakulpong et al 2016), we could readily gather a milligram amount of proteins using this method (16,184 mg/mL), which is sufficient to raise antibodies. Thus, the rCP-SCMV obtained from this study is suitable as a proper antigen.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, rCP-SCMV in highly purified, specific, and high concentration form was obtained with the use of a purification technique based on eletroelution followed by concentrated protein. Comparing our results with those of other similar studies (Abdel-Salam et al 2014;Thanasarasakulpong et al 2016), we could readily gather a milligram amount of proteins using this method (16,184 mg/mL), which is sufficient to raise antibodies. Thus, the rCP-SCMV obtained from this study is suitable as a proper antigen.…”
Section: Discussionsupporting
confidence: 78%
“…The purification process must also maintain the antigenic epitope and the structure of the recombinant protein. Electroelution is used to remove a specific protein of interest from an electrophoresis gel by applying an electric current (Thanasarasakulpong et al 2016). Purification of the recombinant protein was accomplished using electroelution, which enabled a rapid and quantitative elution of proteins from denaturing gels.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,11,13,44,48 For recombinant protein-based vaccines in general, the resulting immunogenicity of the antigen is intrinsically related to the cell line used to express the antigen, as well as the methods used to purify the antigen, which will impact the nature of posttranslational modifications to the antigen and/or the conformation of the antigen, respectively. 49 Nucleic acid vaccination may allow for an improved immune response to conformation dependent antigens such as RSV F because the vaccine antigen is translated by host cells and is then presented to the immune system immediately upon translation. Here we used a mRNA/LNP vaccine platform to compare different forms of RSV F in rodent models and showed that these vaccines were both immunogenic and protective against RSV A and B challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The purification process of the recombinant protein in this study was modified by the electroelution method as described previously (Thanasarasakulpong et al, 2016). Briefly, the cell pellets were lysed in native lysis buffer (50 mM NaH 2 PO 4 , 300 mM NaCl, 10 mM imidazole; pH 8.0), with gentle shaking at 4°C for 1 h. Then, the suspension was centrifuged at 10,000×g at 4°C for 30 min.…”
Section: Preparation Of Romphmentioning
confidence: 99%
“…Our previous studies demonstrated that the outer membrane protein H of P. multocida strain X-73 (serovar A:1) is a capsule-associated antigen and a cross-protective antigen among P. multocida capsular serogroup A strains (Ali et al, 2004a(Ali et al, , 2004bBorrathybay et al, 2003). The recombinant outer membrane protein (rOmpH) of strain X-73 was prepared in Escherichia coli and purified by electroelution (Thanasarasakulpong et al, 2016). Purified rOmpH was formulated with the E. coli heat-labile enterotoxin B (LTB) and inoculated into laying hens via nasal administration (Thanasarasakulpong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%